The story of life in 25 fossils : tales of intrepid fossil hunters and the wonders of evolution - Prothero, Donald R. (Columbia University Press, 2015)
Every fossil tells a story. Prothero recounts the adventures behind the discovery of twenty-five famous, beautifully preserved fossils and explains their significance within the larger fossil record, creating a riveting history of life on our planet.